2013
DOI: 10.1007/s00213-013-3140-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatments prescribed to people with autism spectrum disorder (ASD) in primary health care

Abstract: RationaleAutism spectrum disorders (ASDs) affect 1 % of children, having significant impact on health and social outcomes. Psychotropic medication use by individuals with ASD in the USA increased over time, and polypharmacy occurred in >50 % of those prescribed. In the UK, no psychotropic drugs are approved in ASDs, and little is known about patterns of pharmacological treatment in the ASD population and associated co-morbidities.MethodsWe used The Health Improvement Network, a nationally representative primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
76
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 46 publications
5
76
2
2
Order By: Relevance
“…The transmitting grandmother was found in standardized assessments of adult ADHD traits to be above the 95th percentile for impulsivity traits. Recently, Bowton et al described the transmission of the DAT Val559 variant to two, unrelated male subjects with ASD (49) that was not seen in matched unaffected subjects, extending the possible disease associations to a third disorder with evidence of DA signaling perturbations (50)(51)(52)(53)(54)(55)(56)(57).…”
mentioning
confidence: 99%
“…The transmitting grandmother was found in standardized assessments of adult ADHD traits to be above the 95th percentile for impulsivity traits. Recently, Bowton et al described the transmission of the DAT Val559 variant to two, unrelated male subjects with ASD (49) that was not seen in matched unaffected subjects, extending the possible disease associations to a third disorder with evidence of DA signaling perturbations (50)(51)(52)(53)(54)(55)(56)(57).…”
mentioning
confidence: 99%
“…Likewise, it has been suggested that decreased efficacy and more adverse effects are experienced from psychiatric medications, such as behavioral toxicity with tricyclic antidepressants and social; withdrawal and irritability with methylphenidate, by individuals with ASD [9].…”
Section: Introductionmentioning
confidence: 99%
“…(5) Regarding the grouping of substances, the authors refer to Murray et al (2014). However, this publication does not report any data on grouping of substances by ATC codes…”
mentioning
confidence: 98%
“…We are aware of this limitation; hence, we have specified in the limitation section: BFirstly, as IMS MIDAS is not a patient-based medical record database, we were unable to report the number of patients with ASD who visited physicians in this study.^ We agree that patient-based databases provide more information. Indeed, we used THIN database (electronic patient record database) to evaluate prescribing in patients with ASD in the UK (Murray et al 2014). Unfortunately, as pointed out in Bachmann and Hoffmann's letter, these types of data are rarely available from many other countries.…”
mentioning
confidence: 99%